Effect of Enterprise Risk Management, Leverage, and Company Size on Firm Value - Indra Patanduk, Batara; Ayu Damayanti, Ratna; Juwita Purisamya, Asharin (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The purpose of this study was to test and analyze the effect of corporate risk management, leverage, and company size on firm value, both partially and simultaneously with the research subject of textile and garment subsector companies listed on the Indonesia Stock Exchange. This research uses quantitative methods with secondary data sources. The data analysis technique used is multiple linear regression using the SPSS Version 26 application. The total population that became the subject was 17 companies and a sample of 6 companies. The results of this study indicate that partially corporate risk management has a positive and significant effect on firm value. Leverage has a negative and significant effect on firm value. Company size has a positive and significant effect on firm value. While simultaneously, corporate risk management, leverage, and company size have a significant effect on firm value.